KEANEKARAGAMAN HAMA DAN MUSUH ALAMI PADA TANAMAN PALA (Myristica fragrans HOUTT.) DI ACEH SELATAN - Sumeinika Fitria Lizmah; Agustinur Agustinur (Jurnal Agrotek Lestari, 2020)
The diversity of insects, both pests and natural enemies in each place differently is influenced by environmental factors and technical culture of cultivation. This study aims to determine the diversity of pests and natural enemies in nutmeg plants in South Aceh. Insect sampling was carried out at nutmeg plantations in South Aceh, followed by identification in the Faculty of Agriculture laboratory, Teuku Umar University. Methods of data collection using purposive sampling, using light traps, pit fall traps, yellow traps. The Parameters of this study are number of individuals, families, and insect diversity obtained. The results showed that the abundance of pests and natural enemies in Meukek was higher compared to Samadua. The Shannon-Wiener index shows a variety of pests in Meukek high (H'=3.029) and moderate in Samadua (H'=2,788). While the diversity of natural enemies in both Meukek and Samadua is relatively low, namely H'= 1.230 and H' = 1.049. Planting patterns and crop management affect the abundance and diversity of both pests and natural enemies in both locations. Plantations in Meukek tend to be heterogeneous which are planted with a variety of plantation crops (polyculture) while nutmeg plants in the same two are relatively homogeneous (monoculture of nutmeg). Keywords: diversity, pests, parasitoids, predators, nutmeg